2013
DOI: 10.1371/journal.pone.0068855
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Emotional Partners to Sexual Risk Taking and Violence among Female Sex Workers in Mombasa, Kenya: A Cohort Study

Abstract: ObjectivesTo assess sexual risk-taking of female sex workers (FSWs) with emotional partners (boyfriends and husbands), compared to regular and casual clients. Experiences of violence and the degree of relationship control that FSWs have with emotional partners are also described.DesignCohort study with quarterly follow-up visit over 12-months.MethodsFour hundred HIV-uninfected FSWs older than 16 years were recruited from their homes and guesthouses in Mombasa, Kenya. A structured questionnaire assessed partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 41 publications
9
38
1
Order By: Relevance
“…However, this study found that the rate of consistent condom use with sweethearts remains unacceptably low among FEWs (31.4% of those having sex with sweethearts in the past three months). This finding is in line with findings in several studies in other countries, which found that the rates of consistent condom use with regular, non-commercial partners are consistently lower than the rates in commercial relationships [30, 31]. In this situation, partners of FEWs may potentially become a bridging population for HIV/STI transmission [12, 13].…”
Section: Discussionsupporting
confidence: 88%
“…However, this study found that the rate of consistent condom use with sweethearts remains unacceptably low among FEWs (31.4% of those having sex with sweethearts in the past three months). This finding is in line with findings in several studies in other countries, which found that the rates of consistent condom use with regular, non-commercial partners are consistently lower than the rates in commercial relationships [30, 31]. In this situation, partners of FEWs may potentially become a bridging population for HIV/STI transmission [12, 13].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies,11 12 28 47 our study documents that these adolescent FSWs who were exposed to SGBV are at risk for poorer SRH outcomes including high rates of unwanted pregnancy (52%), abortion (53%) and self-reported symptom of STI (84%). Previously our study identified that only 50% of abortions were performed at safer health facilities, and, importantly, nearly three-quarters (74%) of adolescent FSWs who reported undergoing an abortion had experienced complications from the procedure.…”
Section: Discussionsupporting
confidence: 87%
“…Participants who are married, cohabiting or currently living with a male partner, had an intimate partner in the past year, or ever have had a drug-using intimate male partner were more likely to report SGBV. A cohort study with FSWs in Kenya suggested that the level of relationship control, particularly if those emotional partners dominate the drug supply and/or economic gains, can contribute to unwanted sex or difficulty in negotiating contraception 12. Individual-based, or group-based strategies that could be used to prevent SGBV perpetrated by intimate partners include: training workshops, peer education sessions, creation of safe spaces or improved referral services for clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…21 Intimate partners also play a critical role in sexual behaviors and research from South Africa demonstrates that violence perpetrated by intimate partners is associated with women's high-risk sexual behaviors with intimate partners, as well as with clients. 42 Less than 5% of FSWs who experienced sexual violence in Burkina Faso and Togo reported the event to an authority figure, giving evidence to the lack of power that FSWs have to seek justice for such a violation. Likewise, low reporting of violence to health workers suggests failed access to post-exposure prophylaxis and other HIV prevention methods.…”
Section: Discussionmentioning
confidence: 99%